A simple approach to monitoring technical-tactical load in collaboration-opposition sports - Ignacio Alejandro Costa (Journal of Sports and Physical Activity, 2025)
Background: In collaborative-opposition sports, managing training load is essential to ensure optimal planning and performance development. Among all components, the technical-tactical (TT) aspect is the foundation of the game. However, its high complexity makes it difficult to approach and quantify effectively. Aim: This narrative review aimed to critically analyze existing proposals for TT load management and to synthesize a new, improved alternative to support practitioners in collaborative-opposition sports. Methods: A general search was conducted using Google Scholar to identify the most widely cited non-technological approaches to TT load management. Only proposals that used templates without the aid of technology were included. A critical analysis was performed to examine the strengths and limitations of each identified model. The insights gained were then integrated to formulate a new and more functional proposal. Results: Three relevant proposals using non-technological templates were identified. Each was critically examined, with attention given to their practical contributions and inherent limitations. By integrating the positive aspects of each while addressing their weaknesses, a new TT load management model was developed. Conclusion: The synthesized proposal provides a simple yet ecologically valid tool for managing technical-tactical load in collaborative-opposition sports. Its ease of application and contextual relevance make it a valuable resource for coaches and practitioners seeking effective, accessible methods to support player development.